FORMASI IMAN DAN MODERASI BERAGAMA: TEOLOGIS‑PEDAGOGIS MEMBANGUN SIKAP TOLERAN DALAM KEKRISTENAN DI ERA PLURALISTIK - Ventje Adri Politon; Olivia Cherly Wuwung; Santi Yanti Kalangi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This study examines the integration of faith formation and religious moderation within the context of Christianity as a theological-pedagogical approach to fostering tolerant attitudes in a pluralistic society. Employing a qualitative-descriptive approach based on library research, this paper identifies the theological principles of faith formation such as love (agape), respect for human dignity (imago Dei), and prophetic responsibility alongside the pedagogical principles of religious moderation emphasizing balance, openness, reflection, and dialogue. The integration of these principles produces a conceptual framework applicable to church practices, family life, and Christian educational communities, nurturing faith that is both steadfast and open to diversity. The novelty of this research lies in highlighting the theological dimension of religious moderation within the Christian tradition and its relevance for character formation in today’s digital and multicultural context. Furthermore, the study offers practical directions for developing an inclusive and peace-oriented faith culture within church and social life.